ANALISIS POTENSI PELANGGARAN ETIKA MENUJU PEMILU PARALLEL TAHUN 2024 - Rini T Simangunsong; Dina Mariana Situmeang; Herlina Panggabean (JURNAL RETENTUM, 2023)
The Election Organiser Code of Ethics, in general, is a unified set of moral, ethical, and philosophical principles that serve as a guideline for Election Organisers' behaviour in the form of obligations or prohibitions, actions and/or remarks that are or are not appropriate for Election Organisers to make. The 2024 simultaneous election is a rather challenging election for election organisers, both the KPU and Bawaslu. Where it incorporates the Presidential and Vice- Presidential Elections, the DPR and DPD Elections, as well as the Provincial and Regency/City DPRDs. Of course, this adds complexity to the execution, especially with the recruitment of organisers in the middle of the stage. This article seeks to uncover probable ethical issues in the conduct of elections in Indonesia during the 2024 simultaneous elections. This article is based on library resources, secondary data owned by the author, or data obtained from third parties. Secondary data from available data relating to patterns of ethical infractions is used asthe foundation for analysis. Based on the information gathered, the general public believes that the potential issue of ethical violations in the conduct of elections in Indonesia in the 2024 simultaneous elections will not be far from the fundamental ethical principles of siding with one of the political forces, conflicts of interest, accepting bribes, and becoming opaque. Certain incidents, such as those concerning the KPU and Bawaslu standards of professionalism, violations of the principle of legal certainty, and violations of the principle of independence, are likely to be repeated in the future.